Novel Role of T Cells and IL-6 (Interleukin-6) in Angiotensin II-Induced Microvascular Dysfunction - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2019)
Hypertension is an established risk factor for subsequent cardiovascular diseases, with Ang II (angiotensin II) playing a major role in mediating thrombotic and inflammatory abnormalities. Although T cells and IL-6 (interleukin-6) play an important role in adaptive immune responses, little is known about their role(s) in the thromboinflammatory responses associated with Ang II. Here we show using intravital microscopy coupled with the light/dye injury model that Rag-1 deficient (Rag-1(-/-)) and IL-6 deficient (IL-6(-/-)) mice are afforded protection against Ang II-induced thrombosis. Blocking IL-6 receptors (using CD126 and gp130 antibodies) significantly diminished Ang II-mediated thrombosis and inflammatory cell recruitment in mice. Furthermore, the adoptive transfer of IL-6(-/-)-derived T cells into Rag-1(-/-) mice failed to accelerate Ang II-induced thrombosis compared with Rag-1(-/-)mice reconstituted with wild-type-derived T cells, suggesting T cell IL-6 mediates the thrombotic abnormalities associated Ang II hypertension. Interestingly, adoptive transfer of WT T cells into Rag-1(-/-)/Ang II mice resulted in increased numbers of immature platelets, which constitutes a more active platelet population, that is, prothrombotic and proinflammatory. To translate our in vivo findings, we used clinical samples to demonstrate that IL-6 also predisposes platelets to an interaction with collagen receptors, thereby increasing the propensity for platelets to aggregate and cause thrombosis. In summary, we provide compelling evidence for the involvement of IL-6, IL-6R, and T-cell-dependent IL-6 signaling in Ang II-induced thromboinflammation, which may provide new therapeutic possibilities for drug discovery programs for the management of hypertension.
Keywords: angiotensin II; hypertension; interleukin-6; inflammation; thrombosis; IN-VIVO BIOTINYLATION; RETICULATED PLATELETS; INTERFERON-GAMMA; HYPERTENSION; THROMBOSIS; RECEPTOR; SYSTEM; LEUKOCYTE; ACTIVATOR; INFLAMMATION